Cystathionine γ-lyase downregulation promotes liver injury and necroptosis through reprogramming of methionine cycle - Cichun Wu; Wei Zhang; Wenhu Liu; Zhengshan Tang; Shifang Peng; Lei Fu; Xin Ni (Redox Report, 2025)
Objective Chronic liver diseases (CLDs) are prevalent globally. The purpose of the current study was to elucidate the regulatory mechanisms underlying the pathophysiological processes in CLDs.Methods and Results Using the GEO database, we identified cysteine and methionine metabolism as a commonly enriched pathway in some CLDs. We then confirmed that hepatic cystathionine γ-lyase (Cth), a key enzyme in this pathway, was significantly downregulated in some CLDs in humans and rodent models. Cth-deficient mice exhibited hepatic necroptosis, inflammation and mitochondrial impairment. Omics revealed methionine cycle dysregulation and reduced betaine, a methionine cycle metabolite. Betaine supplementation rewired the methionine cycle, and alleviated necroptosis, inflammation and mitochondrial impairment. Dysregulation of fatty acid β-oxidation, glycolysis and lipid biosynthesis caused by Cth deficiency was improved by betaine. Cth deficiency decreased Pparα, Nrf2, Pgc-1α, and Srebf2 (the transcription factors linked to mitochondria function and metabolism) expression while increasing Irf8 and Irf9, changes reversed by betaine. Histone methylation (H3K9me3, H3K27me3, H3K79me3) decreased, and acetylation (H3K27ac) increased with Cth deficiency, which betaine corrected. Irf8 and Irf9 and Ppara and Ppargc1a expression were regulated by H3K27me3 and H3K79me3 in hepatocytes, respectively.Discussion Our study indicates that CTH is the key factor for maintaining hepatocyte function and survival through homeostasis of the methionine cycle and immediately highlights a new potential target of hepatic protection therapy for some CLDs.